RELATIONSHIP BETWEEN KNOWLEDGE AND INTEREST IN USING MENSTRUAL CUPS IN WOMEN OF REPRODUCTIVE AGE - Marpaung, Zahra Thamizya; I’tishom, Reny; Jayanti, Ratna Dwi (Indonesian Midwifery and Health Sciences Journal, 2025)
Background: Menstrual cups have many advantages compared to other menstrual products but have not been widely used and are less desirable due to limited knowledge. In Indonesia, the majority of women use disposable sanitary napkins as menstrual products because they can be easily found even though the use of sanitary napkins can have a negative impact on health and the environment. The objective of this research is to analyze the relationship between knowledge and interest in using menstrual cup among women of reproductive age. Method: This study was an observational analytic study with a cross sectional approach. The sampling technique used sequential sampling. The sample size studied was 100 women of reproductive age in the service area of Mulyorejo Health Center, Surabaya, Indonesia who met the inclusion criteria. The research instrument used a questionnaire containing a list of questions related to knowledge and interest in using menstrual cups. Data were analyzed using the chi square test. Results: The results of this study showed that out of 100 respondents, 52 respondents (52%) had poor knowledge, 31 respondents (31%) had sufficient knowledge and 17 respondents (17%) had good knowledge. A total of 69 respondents (69%) were not interested in using menstrual cups. The results of the chi square test analysis showed a p value of 0.086 (p> 0.05). Conclusion: There is no significant relationship between knowledge and interest in using menstrual cup.